Gamete Nuclear Migration in Animals and Plants - Fatema, Umma; Ali, Mohammad F.; Hu, Zheng; Clark, Anthony J.; Kawashima, Tomokazu (Frontiers in Plant Science, 2019)
The migration of male and female gamete nuclei to each other in the fertilized egg is a prerequisite for the blending of genetic materials and the initiation of the next generation. Interestingly, many differences have been found in the mechanism of gamete nuclear movement among animals and plants. Female to male gamete nuclear movement in animals and brown algae relies on microtubules. By contrast, in flowering plants, the male gamete nucleus is carried to the female gamete nucleus by the filamentous actin cytoskeleton. As techniques have developed from light, electron, fluorescence, immunofluorescence, and confocal microscopy to live-cell time-lapse imaging using fluorescently-labelled proteins, details of these differences in gamete nuclear migration have emerged in a wide range of eukaryotes. Especially, gamete nuclear migration in flowering plants such as Arabidopsis thaliana, rice, maize, and tobacco has been further investigated, and showed high conservation of the mechanism, yet, with differences among these species. Here, with an emphasis on recent developments in flowering plants, we survey gamete nuclear migration in different eukaryotic groups and highlight the differences and similarities among species.